Memelihara Soft Power Sebagai Landasan Strategi Diplomasi - Trido Saputro (Budapest International Research and Critics University, 2018)
This article examines how soft power run as diplomatic strategy. The writer takes Indonesia and Egypt as the object of the study. Indonesia used soft power strategy to face some accidents while the Arab Spring happened in Egypt, when some Indoensian students are arrested because they are alleged involved in a forbidden organization. This strategy came into effect without many problems. Meanwhile, Egypt after Gamal Abdel Nasser also tends to use soft power strategy to show their interest, internally and internationally.